Access to court interpreting as social inclusion for migrants in Australia: an analysis of courtroom examination questions and answers - Yi, Ran (Comparative Legilinguistics, 2024)
With nearly half of its population born overseas, Australia is one of the most prominent societies built and shaped by migrants worldwide. In Australian courts, access to court interpreting is crucial for social inclusion. However, translating the language of law in court is never an easy job. Therefore, court interpreters serve as indispensable gatekeepers for procedural justice and linguistic equity. But how accurately did court interpreters reproduce lawyer questioning and defendant testimony in court? Drawing on triangulated survey and interpreting performance data, our initial findings suggest a mismatch between what the interpreters said they would do and what the interpreters actually did when translating the manner in which lawyers crafted their questions and defendant responded to their questions in court. Our contributions are three-fold: (1) increasing the linguistic ‘manner awareness’, (2) promoting interprofessional understanding, and (3) compassing future pedagogies in court interpreter education.